Fungal Species Detection in Onychomycosis by Culture and Direct Microscopy at Tertiary Care Hospital, Bahawalpur, Pakistan - Muhammad Wajid Khurshid Sipra, Muhammad Abdul Raziq, Zia Ullah, Muhammad Wajid Khurshid Sipra, Muhammad Abdul Raziq, Zia Ullah (Journal of Rawalpindi Medical College, 2022)
Background: Fungal nail infection is common clinically identified in OPD irrespective of age and gender in our population. The treatment is initiated that mostly resistant to overcome the problem. A mycological confirmation is valuable to eradicate the disease as usefulness of antifungal against particular fungi. The laboratory diagnosis like microscopy and culture to identify the species level. Objective: This study was aimed as comparison of mycological culture with KOH mount microscopy of nail infections. Study Design: comparative cross sectional study. Duration:1st July, 2018 to 31th July 2021 Setting: 360 clinically diagnosed cases collected from Dermatology OPD –removed for blind review— Method: The nail specimen was directly inoculated on SDA culture media and aerobically incubate at 25 Ć to 30 Ć for 3 to 4 weeks. The growth was identified on colony characteristics by using of cotton blue stains. Whereas nail is immersed in 20% KOH solution. Microscopic study was revealed the hyphae or spores and that considered as a positive for test. Result: out of three hundred sixty cases the culture positivity was 56.94% specimen while KOH mount were positive in 60.83% specimens and combination of Culture with KOH were 66.67%. Conclusion: Combination of fungal culture and KOH mount microscopy is subtle laboratory methods for eradication of onychomycosis precisely. The sensitivity of diagnosis that limit the complications and quality of public health considerably raised. Key words: SDA (Sabouraud's dextrose agar), KOH (Potassium hydroxide). Mycological culture and Outpatient Department (OPD).